Electrostatic hazards - Lüttgens, Günter (Butterworth Heinemann, 1997)
In the US, UK and Europe there is in excess of one notifiable dust or electrostatic explosion every day of the year. This clearly makes the hazards associated with the handling of materials subject to either cause or react to electrostatic discharge of vital importance to anyone associated with their handling or industrial bulk use. This book provides a comprehensive guide to the dangers of static electricity and how to avoid them. It will prove invaluable to safety managers and professionals, as well as all personnel involved in the activities concerned, in the chemical, agricultural, pharmac.
Keywords: Industrial buildings -- Fires and fire prevention.; Electrostatics.; Industrial accidents -- Case studies.; Static electricity and fires.; elektronické knihy; electronic books